Speech considerations in prosthodontic rehabilitation of the glossectomy patient - Mckinstry, Robert E; Aramany, Mohamed A; Beery, Quinter C; Sansone, Frank (Journal of Prosthetic Dentistry, 1985)
A knowledge of normal articulation is needed before the prosthodontist can assess the compensatory articulation used by glossectomy patients. The amount and portion of tongue resected is directly correlated with speech intelligibility. The loss of the tip of the tongue is more critical to intelligibility than a hemiglossectomy. Partial glossectomy speakers can often use the residual tongue stump to perform adaptive movements that approximate normal movements and should be treated as an articulation problem. The compensatory articulation used by the total glossectomy patient was reviewed. The prosthodontic management of patients with partial tongue resection often includes lowering the palatal vault, while the management of the total glossectomy patient usually requires a mandibular tongue prosthesis. These prostheses can be refined with the use of multiview videofluoroscopy, videotaping, and spectrographic analysis. © 1985.
Keywords: Dentures; Glossectomy; Human; Mandible; Prostheses and Implants; Prosthesis Design; Speech Articulation Tests; Speech Disorders; Tongue; article; denture; dept.cmd; glossectomy; human; mandible; prostheses and orthoses; prosthesis; speech analysis; speech disorder; tongue